2013
DOI: 10.7567/jjap.52.09ld03
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Diffusion Technique for Suppressing Interpage Crosstalk in Holographic Data Storage

Abstract: To suppress interpage crosstalk that strongly restricts holographic data storage capacity, a digital image diffusion technique was proposed. In this technique, signal and crosstalk components are separated from the propagation angle difference produced by using a random diffuser and the nature of phase conjugate lights. The most attractive feature of the technique is that crosstalk suppression can be conducted while mostly keeping the conventional holographic data storage system unchanged by integrating optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This is because the noise from an undesired hologram was reduced by the random diffuser. 34) Thus, by comparing the red and blue lines in Fig. 9, we can confirm the pure effect of the proposed method in which multiple data pages are simultaneously recorded.…”
Section: Effect On Recording Densitymentioning
confidence: 55%
“…This is because the noise from an undesired hologram was reduced by the random diffuser. 34) Thus, by comparing the red and blue lines in Fig. 9, we can confirm the pure effect of the proposed method in which multiple data pages are simultaneously recorded.…”
Section: Effect On Recording Densitymentioning
confidence: 55%
“…Thus, modal cross-talks (MXTs), which are called interpage XTs in the HDS, are generated from nonreconstruction holograms. 24) Therefore, the mode separation performance of the VHDM is degraded because of the intensity overlap between spatial modes. Previous studies have indicated that the separation performance with a large overlap is lower than that with a small overlap, thereby supporting the aforementioned assertion.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplexed recording by use of a double-random phase encryption [13] can eliminate a part of this crosstalk. The crosstalk is diffused with a conjugate reconstruction and a random diffuser in a Fourier plane [14,15]. This method, however, makes an optical system complicated due to the requirement for a random diffuser and its precise alignment.…”
mentioning
confidence: 99%